(untitled) (Fiep Bulletin - online, 2015)
This work aimed the comprehension of the the strategies used by media to build and maintain the image in highlights of the idol of Brazilian football, Neymar Júnior. For both, the raw Globoesporte.com news site and its mechanisms of media scheduling from three categories were analyzed: the professional practice, personal life and the declaration of personalities on the Brazilian playmaker. For such categorization and inference method and the qualitative technique of content analysis was used. Great deeds and creating linkages are fundamental to the construction of the sports idol; achievements extolled by the media and the ties of belonging perpetuate the positive image of the athlete before his audience, which has hitherto player Neymar as the main name Brazil for winning the 2014 World Cup.